Revisiting L2 pragmatic competence through implicit vs. explicit instructional framework - Huang, Nan (Frontiers in Psychology, 2022)
Successful interaction in the target language requires L2 learners to use and understand the grammatically correct language. At the same time, the language used is expected to produce socioculturally appropriate utterances that it refers to their Pragmatic competence. The latter entails acquiring pragmatic competence, which has proved to be very challenging for L2 learners. This is because they gain limited exposure to the use of language for real communication in an authentic social setting. Moreover, instruction has been found to influence the functional abilities in L2 as it equips the learners with the ability to produce and comprehend L2 in different situations. Focusing on the research conducted on the role of explicit and implicit instruction on L2 pragmatic competence, this study aimed to give a summative description of the empirical studies carried out on teaching pragmatics. The investigation ends up with a conclusion, instructional implications, and suggestions for future research.